Moiré Lattice of Twisted Bilayer Graphene as Template for Non-Covalent Functionalization - Dierke, Tobias; Wolff, Stefan; Gillen, Roland; Eisenkolb, Jasmin; Nagel, Tamara; Maier, Sabine; Kivala, Milan; Hauke, Frank; Hirsch, Andreas; Maultzsch, Janina (Angewandte Chemie International Edition, 2025)
Keywords: 2D materials; Graphene; Raman spectroscopy; Density functional calculations; Functionalization

Spatial Control of Graphene Functionalization by Patterning a 2D Substrate: Implications for Graphene Based van-der-Waals Heterostructures - Dierke, Tobias; Dasler, Daniela; Nagel, Tamara; Hauke, Frank; Hirsch, Andreas; Maultzsch, Janina (ACS Applied Nano Materials, 2022)
We present an experimental study on the degree of covalent functionalization of graphene exfoliated on top of hBN stripes on Si/SiO2as well as on other two-dimensional (2D) materials. The underlying substrate has a strong effect on the degree of functionalization of graphene. Our results indicate that the functionalization of graphene is less effective on hBN than on SiO2, as shown by higher defect-induced modes in the graphene Raman spectra on SiO2. Other underlying 2D materials like MoS2, WS2, and MoO3show less contrast in functionalization density than hBN or lead to even higher degree of functionalization than the Si/SiO2substrate. Patterning the underlying material is therefore a versatile method for spatially defined functionalization of graphene because it preserves the intrinsic high-quality properties of graphene, a clear advantage over other patterning approaches based on masks or introduction of defects. Our work shows that the rich variety of 2D materials offers numerous possibilities to integrate graphene with different degrees of functionalization into van-der-Waals heterostructures and devices.
CRIS-Team Scopus Importer:2022-05-13
Keywords: 2D materials; functionalization pattern; graphene; hBN; Raman spectroscopy; van-der-Waals heterostructures